The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/pssa.201700565
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silicon Nanowire Arrays for Reversible Optical Gas Sensing

Abstract: Porous silicon nanowire arrays are shown to be used for optical detection of molecular oxygen (O 2 ). The samples are produced by metal assisted chemical etching of heavily boron-doped wafers of crystalline silicon. It is found that the photoluminescence signal from porous silicon nanowires quenched in O 2 ambience but restored again in N 2 atmosphere, which repeated in several cycles. Electron paramagnetic resonance data demonstrate that number of silicon dangling bonds (Pb-center) increases after O 2 adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In recent years, nano-Si has been widely used for optical (bio)sensor applications due to its portability and high sensitivity. Among all of the optical detection approaches, photoluminescence (PL)-based measurement looks the most promising, especially for real-time monitoring [3,18,19,72,78,81,82,83,84]. Previously, we reported on low-cost, highly sensitive PSi-based immunosensors for ochratoxin A (OTA) detection using a PL approach.…”
Section: (Bio)sensors Based On Psi Sinws Sinps and Their Composimentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, nano-Si has been widely used for optical (bio)sensor applications due to its portability and high sensitivity. Among all of the optical detection approaches, photoluminescence (PL)-based measurement looks the most promising, especially for real-time monitoring [3,18,19,72,78,81,82,83,84]. Previously, we reported on low-cost, highly sensitive PSi-based immunosensors for ochratoxin A (OTA) detection using a PL approach.…”
Section: (Bio)sensors Based On Psi Sinws Sinps and Their Composimentioning
confidence: 99%
“…The sensor mechanism was based on the effect of PL changing with the varying pH of the solution caused by the enzymatic reactions [18]. Furthermore, it was reported that the PL-based detection approach could be utilized for O 2 detection on a SiNW platform [84]. SiNWs were fabricated by the MACE method and O 2 detection was carried out through the measurement of different oxygen flow pressure.…”
Section: (Bio)sensors Based On Psi Sinws Sinps and Their Composimentioning
confidence: 99%
“…The surface of the nanowires is coated with a thin oxide layer, which is formed during their preparation. This oxide layer protects the nanowires from further oxidation due to contact with environmental molecules, including atmospheric gases and water under normal environmental conditions [13,14]. The properties of light interference in the layers of Si NWs shown can be used to detect protein A and sucrose [15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the possibility of using silicon nanowires (SiNWs) in sensorics (Cui et al, 2001; Wang and Ozkan, 2008; Cao et al, 2015; Georgobiani et al, 2018), photovoltaics (Kelzenberg et al, 2008; Stelzner et al, 2008; Sivakov et al, 2009), photonics (Brönstrup et al, 2010), and micro-and optoelectronics (Föll et al, 2010; Yang et al, 2010) has been shown. Nanowires are usually obtained as a result of anisotropic growth of a 1D crystal on a nanometer scale.…”
Section: Introductionmentioning
confidence: 99%